PROTEUS - promoting success in university: a results assessment - Pinto, Joana Carneiro; Ramalho, Susana Costa; Branquinho, Cátia (Frontiers in Education, 2025)
IntroductionThe promotion of success in higher education has been extensively researched, with decades of studies contributing to a substantial body of knowledge on the topic. Research indicates that reducing dropout rates and fostering academic success require a comprehensive understanding of the intricate interactions between individual, social, and institutional factors. Specifically, regarding institutional factors, it is important to enhance resources, facilitating both academic and social integration, and promoting students’ motivation and skill development as key areas for intervention. While some factors influencing student success may lie beyond the control of higher education institutions, there are critical aspects that can be shaped to create a more supportive environment conducive to student achievement.MethodThis paper outlines a series of initiatives designed in line with these findings and tailored to the institutional context in which they were implemented. These efforts are part of the PROTEUS project — Promoting Success in University — funded by Portugal’s Directorate General for Higher Education. It also presents results from a quantitative study evaluating two distinct cohorts of first-year students: one group assessed prior to the implementation of these initiatives (Wave 1; n = 265), and a separate group assessed after their implementation (Wave 2; n = 115). The evaluations in both waves focused on key areas such as academic experiences, overall well-being, psychological well-being, and health behaviors.ResultsResults indicate that in comparison to the pre-intervention cohort (Wave 1), students in the post-intervention cohort (Wave 2) reported improvements in academic integration, psychological well-being, and health-related behaviors.DiscussionThese findings suggest that the PROTEUS project contributed to a more supportive academic environment and enhanced student outcomes. The main conclusion is that targeted institutional interventions can effectively promote student success and reduce dropout risk.